Liabilities and remedies of the changed circumstances caused by the COVID-19 in construction projects around the world - Wei, He (2020)
Essentially, the loss suffered by the global construction industry during the time when the COVID-19 is spread is not caused by that pandemic itself but caused by a changed circumstance which mainly resulted by anti-COVID-19 policy or law conducted by different jurisdictions. Where contract keeps silent in this regard, legal solution should be made by contemplating the law in different jurisdictions toward changed circumstances, which commonly includes situations where performance of contract become more onerous or impossible, and taking account of the factual environment which determines or impacts the changed circumstance. This paper, from a comparative law perspective, discusses and concludes the doctrine of changed circumstance in some typical jurisdictions, and, by taking consideration of law and fact, provides some approaches and potential legal solutions to deal with that loss.